2006
DOI: 10.1007/s10447-005-9009-7
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Productivity of Editorial Board Members of Three American Counseling and Counseling Psychology Journals

Abstract: The scholarly journals in professional and scientific fields serve the function of communicating new knowledge and informed discourse on the major issues affecting the field of counseling, and editorial board members (EBMs) serve as gatekeepers of what information will be communicated. The ability of EBMs to make sound judgments directly affects the quality of research and scholarship published. This study analyzed one important EBM qualification, the scholarly productivity of the editorial board members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…The correlation of institutional research productivity and the ranking in U.S. News and World Report ranged from .57 to .64. In another study, Weinrach, Thomas, Pruett, and Chan (2006) used PsycINFO to calculate the total number of articles published by editorial board members in three counseling journals: The Counseling Psychologist ( TCP ), the Journal of Counseling Psychology ( JCP ), and the Journal of Counseling and Development ( JCD ). Board members of JCP had the highest scores, followed by those of TCP and then JCD , suggesting that the selection of board members is based on different criteria for each journal.…”
Section: Six Methods Of Measuring Productivitymentioning
confidence: 99%
“…The correlation of institutional research productivity and the ranking in U.S. News and World Report ranged from .57 to .64. In another study, Weinrach, Thomas, Pruett, and Chan (2006) used PsycINFO to calculate the total number of articles published by editorial board members in three counseling journals: The Counseling Psychologist ( TCP ), the Journal of Counseling Psychology ( JCP ), and the Journal of Counseling and Development ( JCD ). Board members of JCP had the highest scores, followed by those of TCP and then JCD , suggesting that the selection of board members is based on different criteria for each journal.…”
Section: Six Methods Of Measuring Productivitymentioning
confidence: 99%
“…The academic reputation of a journal will be strongly influenced by the reputations of its EBMs, and it would hence appear mandatory for them to have a demonstrable track record of research, typically as demonstrated by high levels of publication, citation and funding. However, studies of leading journals in several professional subjects (accountancy (Lowe & van Fleet, 2009), counselling (Weinrach, Thomas, Pruett, & Chan, 2006), finance (Hardin, Liano, Chan, & Fok, 2008), management (Bedeian, van Fleet, & Hyman, 2009b), and social work (Pardeck, 1992)) suggest that this is not always the case, with some EBMs demonstrating levels of scholarly achievement notably less than might have been expected. Such studies are, hardly surprisingly, quite controversial (Bedeian, van Fleet, & Hyman, 2009a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Weinrach et al. (2006) pointed out,
The scholarly journals in professional and scientific fields serve as the primary means of communicating new knowledge and informed discourse on the major issues affecting the field. As such, these journals wield significant influences on what information will be incorporated into the foundational knowledge of the profession.
…”
Section: Introductionmentioning
confidence: 99%
“…To discharge this responsibility, editorial board members need to have extensive experience with the process of research and the dissemination of scholarly findings (Weinrach et al., 2006).…”
Section: Introductionmentioning
confidence: 99%